Implications of worsening renal function before hospitalization for acute heart failure. (3rd November 2022) - Wettersten, Nicholas; Duff, Stephen; Horiuchi, Yu; van Veldhuisen, Dirk J.; Mueller, Christian; Filippatos, Gerasimos; Nowak, Richard; Hogan, Christopher; Kontos, Michael C.; Cannon, Chad M.; Müeller, Gerhard A.; Birkhahn, Robert; et al.
Abstract: Aims: Kidney function changes dynamically during AHF treatment, but risk factors for and consequences of worsening renal function (WRF) at hospital admission are uncertain. We aimed to determine the significance of WRF at admission for acute heart failure (AHF). Methods and results: We evaluated a subgroup of 406 patients from The Acute Kidney Injury Neutrophil gelatinase–associated lipocalin Evaluation of Symptomatic heart failure Study (AKINESIS) who had serum creatinine measurements available within 3 months before and at the time of admission. Admission WRF was primarily defined as a 0.3 mg/dL or 50% creatinine increase from preadmission. Alternative definitions evaluated were a ≥0.5 mg/dL creatinine increase, ≥25% glomerular filtration rate decrease, and an overall change in creatinine. Predictors of admission WRF were evaluated. Outcomes evaluated were length of hospitalization, a composite of adverse in‐hospital events, and the composite of death or HF readmission at 30, 90, and 365 days. Biomarkers' prognostic ability for these outcomes were evaluated in patients with admission WRF. One‐hundred six patients (26%) had admission WRF. These patients had features of more severe AHF with lower blood pressure, higher BUN, and lower serum sodium concentrations at admission. Higher BNP (odds ratio [OR] per doubling 1.16–1.28, 95% confidence interval [CI] 1.00–1.55) and lower diastolic blood pressure (OR 0.97–0.98, 95% CI 0.96–0.99) were associated with a higher odds for the three definitions of admission WRF. The primary WRF definition was not associated with a longer hospitalization, but alternative WRF definitions were (1.3 to 1.6 days longer, 95% CI 1.0–2.2). WRF across definitions was not associated with a higher odds of adverse in‐hospital events or a higher risk of death or HF readmission. In the subset of patients with WRF, biomarkers were not prognostic for any outcome. Conclusions: Admission WRF is common in AHF patients and is associated with an increased length of hospitalization, but not adverse in‐hospital events, death, or HF readmission. Among those with admission WRF, biomarkers did not risk stratify for adverse events.